Urgensi Kompetensi Profesional Guru dalam Menguasai Materi IPS di Sekolah Dasar - Syahla Rizkiya Putri N; Siti Zahra Al Munawaroh; Tin Rustini (Departement of Mathematics Education, 2022)
The world of education can not be separated from the figure of a teacher. The teacher is a professional educator whose job is to educate and guide students to become intelligent and skilled individuals in various ways. The roles of teachers and students are always side by side in the world of education, therefore teachers and students are two important components in the world of education. A good teacher is a teacher who is able to carry out his duties properly, in this case a teacher must understand and carry out various kinds of competencies that exist and must be achieved by a teacher. One of the competencies that must be possessed by teachers is professional competence, which means that a teacher must have a broad and deep mastery of learning materials so that learning can run well and achieve learning objectives. A teacher must be able to have good professional competence in various fields of learning. One of the learning materials found at the elementary school level is social studies learning material. At the elementary school level, students' thinking patterns are still abstract, while the scope of social studies material is very broad, therefore it is important for a teacher to be able to master his professional competence, especially in social studies material in elementary schools.